SOPHIA PHILIA AS A SPIRITUAL PRACTICE (Analele Universității București.Filosofie, 2025)
Philosophy can be understood as a spiritual practice because the purpose of philosophizing is the cultivation of the spiritual in man, of what can be subject to improvement, and change through reorientation and purification through the recurring act of intervention-cultivation. The effect of the practice of philosophy is not a mere improvement of the inner life, but a radical reorientation of the intentions under which it takes place. Philosophy, as a daily replayed act, means reworking inner paths, repetitively but not in the same way.